2011
DOI: 10.3141/2228-01
|View full text |Cite
|
Sign up to set email alerts
|

Performance Bond Benefit–Cost Analysis

Abstract: A performance bond provides the assurance that an awarded construction project will be satisfactorily completed in the event that the contractor is unable to complete the project as agreed and the contract is terminated. First passed into U.S. law in the late 1800s, performance bonds protect against financial losses. The ability of contractors to provide a performance bond has mistakenly been assumed as a guarantee that contractors will perform well on the projects they are awarded. Indications are that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, the DOT receives financial benefits from a performance bond only after a claim is filed. A nationwide study on the costeffectiveness of performance bonds across 30 states provided data for 19,135 projects (Table 3) and revealed that the 2007-2009 U.S. national average of bond premiums was 1.139% (12). Only six states reported contractor defaults in that period.…”
Section: Benefits Of Performance Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the DOT receives financial benefits from a performance bond only after a claim is filed. A nationwide study on the costeffectiveness of performance bonds across 30 states provided data for 19,135 projects (Table 3) and revealed that the 2007-2009 U.S. national average of bond premiums was 1.139% (12). Only six states reported contractor defaults in that period.…”
Section: Benefits Of Performance Bondsmentioning
confidence: 99%
“…Thus it forms a metric to measure the potential for default as a result of the inability to pay bills when due. A new business is doubly disadvantaged by the current performance bonding system because its net assets and net cash typically are low (2). Well-publicized federal and state mandates are meant to stimulate the growth of new small business enterprises (15).…”
Section: Impact On Small Contractorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of benefit-cost is viewed from the perspective of whole society, which is ensured to identify a best alternative and to achieve the largest social fringe benefit (Myers et al, 2011). Since the role of public investment is to promote the social fringe benefit, the cost-benefit is used in appraisal of public projects, and this becomes a classical method, which is applied into many fields (Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The performance guarantee policies are designed to safeguard against performance risks, as the government will confiscate the guarantee money if the SPV fails to provide the predetermined services [15]. Myers and Najafi analyzed the benefit-cost of performance guarantee for avoiding project default [16]. Shi et al found that the performance guarantee is effective in deterring the strategic breach of contract by the SPV in transport PPP infrastructure projects [17].…”
Section: Literature Reviewmentioning
confidence: 99%